PROFIL BISNIS USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SELAMA PANDEMI COVID-19 DI DESA CIKAKAK KECAMATAN CIKAKAK KABUPATEN SUKABUMI - NIRA AKTAVIANA; Anisa Awalia; Nyai Holilah; Vini Silviani; Azis Muslim (Jurnal Abdi Nusa, 2023)
The economic crisis due to the weakening global economy caused by the Covid-19 pandemic poses a major threat to economic sustainability in Indonesia. The purpose of this study was to determine the profile of UMKM in Cikakak Village, Cikakak District, Sukabumi Regency and to find out the problems faced by UMKM actors affected by Covid-19. Methods of data analysis using descriptive qualitative statistical analysis. The results showed that, UMKM in Cikakak Village, Cikakak District, Sukabumi Regency were mostly engaged in the food and beverage sector and used capital from SMEs and personal capital. The obstacles faced by UMKM actors are: rising prices of basic commodities, unstable buying and selling processes, and extreme weather changes. In conclusion, UMKM actors in Cikakak Village still use manual sales processes and there is a need for guidance on the use of digital marketing to promote and market products/services so that they can expand the market.